Multiple system atrophy: natural history, MRI morphology, and dopamine receptor imaging with 123IBZM-SPECT. Issue 9 (September 1994) - Schulz, J B; Klockgether, T; Petersen, D; Jauch, M; Müller-Schauenburg, W; Spieker, S; Voigt, K; Dichgans, J
Abstract : Sixteen patients with a clinical diagnosis of probable multiple system atrophy (MSA) were examined clinically by MRI and by 123I-iodobenzamide single photon emission computed tomography (IBZM-SPECT). The clinical records of another 16 patients were also analysed retrospectively. On the basis of their clinical presentation, patients were subdivided into those with prominent parkinsonism (MSA-P, n = 11) and those with prominent cerebellar ataxia (MSA-C, n = 21). Autonomic symptoms were present in all patients and preceded the onset of motor symptoms in 63% of patients. Calculated median lifetime and the median time to become wheelchair bound after onset of disease were significantly shorter for MSA-P than for MSA-C (lifetime: 4.0 v 9.1 years; wheelchair: 3.1 vs 5.0 years) suggesting a better prognosis for cerebellar patients. A significant loss of striatal dopamine receptors (below 2 SD threshold) was detected by IBZM-SPECT in 63% of the patients (56% below 2.5 SD threshold). There was no difference between patients with MSA-C and those with MSA-P in the proportion with significant receptor loss and the extent of dopamine receptor loss. Planimetric MRI evaluation showed cerebellar and brainstem atrophy in both groups. Atrophy was more pronounced in patients with MSA-C than in those with MSA-P. Pontocerebellar hyperintensities and putaminal hypointensities on T2 weighted MRI were found in both groups. Pontocerebellar signal abnormalities were more pronounced in MSA-C than in MSA-P, whereas the rating scores for area but not for intensity of putaminal abnormalities were higher in MSA-P. MRI and IBZM-SPECT provide in vivo evidence for combined basal ganglia and pontocerebellar involvement in almost all patients in this series.